Scientific English in nursing sciences and health techniques: Attitudes and language needs of teachers in Morocco - Ihrai, Laila; El Abderrahmani, Abdellatif; Lemayet, Mhammed; Merabti, Abdelilah; Mahla, Tarik; Filali Zegzouti, Younes; El Ouali Lalami, Abdelhakim (Jurnal Cakrawala Pendidikan, 2025)
English is still the most dominant foreign language in non-English-speaking countries. Consequently, mastering it at a decent level is a key tool for communication and an invaluable qualification for university teaching. In the Moroccan university educational system, very few academic studies have been conducted on this topic. The present study was designed both to take an overview of the current situation and to assess the real and operational needs in terms of professional use for this language in teaching. A cross-sectional study was implemented among a random sample of 200 teachers practicing at the Higher Institutes of Nursing and Technical Health Professions in Morocco. The survey recorded a high response rate (92%), reflecting the importance of this topic amongst the study population. The participants prioritized the language skills of reading and writing over listening and speaking. Teachers’ attitudes and needs towards English differ greatly according to their socio-demographic and academic backgrounds. PhD candidates, for reasons related to their scientific research, are the most likely to be interested in improving their English skills. The teaching staff in Nursing Sciences, Health Techniques are aware of the value that scientific English can contribute. However, their overall level of English tends to be low. To make up for language deficiencies, all teachers, especially those involved in academic research, are advised to enroll in English courses adapted to their level.